The Geography of Value Creation - Dougal, Casey; Parsons, Christopher A; Titman, Sheridan (Review of Financial Studies, 2022)
Over the last 20 years, the stock market indicates that value creation has become heavily concentrated in a few headquarter cities. At the same time, firms in value-creating cities have experienced declines in their profitability, because of large increases in wages and rents. Our findings thus highlight the difference between flow-based (e.g., operating profits) and stock-based (e.g., securities prices) indicators of local productivity. Conventional proxies for a city’s appeal to high value-added workers, such as education rates and weather, are positively related to stock market valuations, but negatively related to near-term operating performance.